Understanding Local and Global Contexts: The Importance of the Sociological Imagination for Adult Education - Patrica A. Gouthro (Adult Education Research Conference, 2005)
The concept of the sociological imagination is explored as a practical theoretical concept to provide insight into local and global contexts in adult education.